Strategi Meningkatkan Partisipasi Masyarakat Dalam Pilkada Serentak 2020 di Masa Pandemi Covid-19 - Salsabila Yumna Fadhila; Dewi Erowati (Politea : Jurnal Politik Islam, 2021)
This article will discuss the covid-19 pandemic has become one of the most serious problems in holding the 2020 simultaneous regional elections. These conditions have the potential to reduce voter turnout, therefore the strategy to increase public participation needs to be implemented even more strongly. In the 2020 simultaneous regional elections, the KPU has set a national voter turnout target of 77.5%. As an effort to achieve this target, the KPU has implemented a strategy to increase public participation as voters. Qualitative methods are used in this article, and data collection techniques are used through interviews with Head of the Technical and Public Relation Subdivision of the General Election Commissin of Central Java, Dimas Dwihangga Narotama, S.IP and documentation. The results and discussion revealed that the KPU implemented a strategy of maximizing socialization through social and virtual media by holding webinars. However, in-person or face-to-face socialization is still carried out by reducing the number of activities and participants and still paying attention to health protocols. The implementation of strategies through social media or online is more dominant in efforts to increase community participation carried out by each Regency / City KPU in Central Java in the 2020 simultaneous regional elections.